Fabrication and characterization of flexible solar cell from electrodeposited Cu2O thin film on plastic substrate. (December 2015) - Abdelfatah, Mahmoud; Ledig, Johannes; El-Shaer, Abdelhamid; Wagner, Alexander; Sharafeev, Azat; Lemmens, Peter; Mosaad, Mohsen Mohamed; Waag, Andreas; Bakin, Andrey
Graphical abstract: The manufactured flexible AZO/ZnO/Cu2 O solar cell module with round solar cells on top of the gold electrode on plastic foil. The plastic foil covered by 30 nm of Ti as an adhesion layer and 300 nm of Au, both deposited by e-beam evaporation. Electrodeposition of the Cu2 O film was carried out in a three electrode cell equipped from a lactate-stabilized copper sulfate aqueous. Thin buffer layer of 5 nm ZnO was inserted by ALD to improve the junction confinement. Highlights: Electrodeposited Cu2 O thin film flexible solar cell. Thin buffer layer inserted by Atomic Layer Deposition. A power conversion efficiency of 0.904% was achieved for the solar cell. New a promising approach to fabricate lightweight flexible photovoltaic cells. Abstract: We present here for the first time the fabracition of a p-Cu2 O/ZnO/AZO flexible heterojunction solar cell by electrodeposition of Cu2 O thin film on a plastic substrate and sputtering of ZnO:Al layer. The Atomic Layer Deposition (ALD) has been employed to insert 5 nm ZnO as buffer layer. The heterojunction solar cell was characterized by Raman spectroscopy and scanning electron microscopy that show pyramidal shape and phonon modes for Cu2 O thin film. Current–voltage ( J – V ), capacitance–voltage ( C – V ) and the external quantum efficiency (EQE) measurements were performed to understand the heterojunction properties. The solar cell device exhibits a power conversion efficiency of 0.897 ± 0.005% with an open circuit voltage of V oc = 300 mV, a short circuit current density of J sc = 6.819 ± 0.048 mA cm −2 and a fill factor of FF = 0.439 ± 0.006. The values of the built-in potential and the acceptor concentration at the junction were estimated from the reverse bias C – V measurement to be 0.37 V and 6.67 × 10 16 cm −3, respectively.